2019
DOI: 10.1088/1742-6596/1338/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Dijkstra’s Algorithm to Find Shortest Path of Tourist Destination in Bali

Abstract: Bali is one of many small island in Indonesia and referred as “The Island of Gods”. Bali has varieties of tourist destination e.g. art villages, ecotourism, historical building, spiritual tourism and temples. Dijkstra’s algorithm is an algorithm that used to be solution in finding shortest path problem. It can be use to find the shortest route between one tourist destination and all other tourist destinations. Hence, we use dijkstra’s algorithm to find shortest path of tourist destination in Bali. There are to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In tourism research, shortest-path algorithms such as the Dijkstra and A* algorithms have typically been used to plan tour routes with the shortest traveling distances. They have the benefits of being easily accessed and applied [40][41][42]. In addition, the shortestpath algorithms were also constrained by tourism factors such as features and spatial attributes.…”
Section: Selecting and Confirming Of The Control Algorithmsmentioning
confidence: 99%
“…In tourism research, shortest-path algorithms such as the Dijkstra and A* algorithms have typically been used to plan tour routes with the shortest traveling distances. They have the benefits of being easily accessed and applied [40][41][42]. In addition, the shortestpath algorithms were also constrained by tourism factors such as features and spatial attributes.…”
Section: Selecting and Confirming Of The Control Algorithmsmentioning
confidence: 99%
“…The greedy approach means selecting the option or solution that appears to be the greatest at the time. [12]. It merely means selecting the option or solution that appears to be the greatest at the time.…”
Section: B Shortest Path Algorithmmentioning
confidence: 99%
“…The robots must take the shortest possible path to collect/deliver the products to avoid time loss and save energy [26]. Therefore, path-finding algorithms such as Greedy [12] and A* [13] were used to find the shortest path. Since CPS interact with the environment, another problem that may be encountered is the possibility of robots hitting any obstacle that may come their way in the warehouse.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen criteria were chosen for a multicriteria evaluation of the region's tourism potential. The result of AHP method weight scoring showed the internal potential is more important than the external potential, and the multicriteria assessment of regional tourism potential showed that the Central Highlands have several interesting destinations [5,22,23].…”
Section: Related Workmentioning
confidence: 99%